2012
DOI: 10.1084/jem.20111783
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathogenic role of the ER chaperone GRP78/BiP in rheumatoid arthritis

Abstract: The ER chaperone GRP78/BiP is crucial for the development of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 55 publications
5
123
0
Order By: Relevance
“…These properties are quite distinct from those displayed by intracellular, endoplasmic reticulum localized BiP, which regulates the unfolded protein response and induces cytoprotective and anti-apoptotic signals when cells are challenged by endoplasmic reticulum stress [25]. Thus, intracellular BiP may augment chronic inflammation through anti-apoptotic protection of inflammatory cells, such as the rheumatoid fibroblast-like synoviocyte [26] yet, as an extracellular protein, regulate inflammation on secretion from stressed cells [16]. A more complete dissection of the relative contributions of intracellular and extracellular BiP to the pathogenesis and resolution of chronic inflammation will require greater understanding of cells transduced by lentiviral vectors, the receptor or receptors to which BiP binds on the cell surface and the downstream signalling pathways employed.…”
Section: Discussionmentioning
confidence: 99%
“…These properties are quite distinct from those displayed by intracellular, endoplasmic reticulum localized BiP, which regulates the unfolded protein response and induces cytoprotective and anti-apoptotic signals when cells are challenged by endoplasmic reticulum stress [25]. Thus, intracellular BiP may augment chronic inflammation through anti-apoptotic protection of inflammatory cells, such as the rheumatoid fibroblast-like synoviocyte [26] yet, as an extracellular protein, regulate inflammation on secretion from stressed cells [16]. A more complete dissection of the relative contributions of intracellular and extracellular BiP to the pathogenesis and resolution of chronic inflammation will require greater understanding of cells transduced by lentiviral vectors, the receptor or receptors to which BiP binds on the cell surface and the downstream signalling pathways employed.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is another common factor for vascular remodeling under various physiological and pathological conditions, which can not only specifically promote vascular endothelial cell proliferation and angiogenesis, but also change the extracellular matrix. It has been shown that GRP78 can promote angiogenesis directly, or indirectly, through the VEGF pathway (Raiter et al, 2010; Yoo et al, 2012). In this study, we found that the expression levels of FVIII-RAg and VEGF in lung tissues gradually increased as the disease progressed, and the increased GRP78 were positively correlated with the elevated FVIII-Rag and VEGF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the endoplasmic reticulum (ER) stress‐associated protein GRP78/BiP is described as a potential autoantigen. The ER stress response is increased in RA synovial tissue and fluid and the ER chaperone, GRP78, is important for synoviocyte proliferation and angiogenesis, which are substantial indicators of RA …”
Section: The Problem Of Targeting Autoantigen(s) – Which Ones?mentioning
confidence: 99%